2008
DOI: 10.1115/1.2971052
|View full text |Cite
|
Sign up to set email alerts
|

La 0.8 Sr 0.2 Co 0.8 Fe 0.2 O 3 Nanoparticles Formed in Micropores of La0.8Sr0.2MnO3–Yttria Stabilized Zirconia Cathodes

Abstract: La 0.8 Sr 0.2 Co 0.8 Fe 0.2 O 3 (LSCF) nanoparticles are formed in micropores of La0.8Sr0.2MnO2(LSM)-yttria stabilized zirconia (YSZ) cathodes by reaction-infiltration method. Bismuth nitrate is added in the precursor nitrate solution for LSCF as the reaction promoter. The LSCF phase is observed at 600°C by the addition of bismuth nitrate, and about 100nm particle size LSCF(Bi) is homogenously distributed on the LSM-YSZ surface. The electrode impedance of LSM-YSZ/YSZ/LSM-YSZ cells is examined and has found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…There is one report of infiltrated LSCF improving the ohmic impedance of LSM-YSZ; however, the improvement was overshadowed by a much larger improvement in the reaction impedance. 14 Although we observed that infiltrating a cobaltite with high electrocatalytic activity and oxygen ion conductivity lowered the cathode reaction impedance more than nanoYSZ, the combination of lower reaction and lower bulk charge transport impedance with nanoYSZ resulted in superior performance. While structural stability of nanoparticles is often a point of concern for performance degradation, here we show that the performance of the cell modified with nanoYSZ was three times more stable than that of the cell with PBC (Pr x Ba 1−x CoO 3−δ ).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…There is one report of infiltrated LSCF improving the ohmic impedance of LSM-YSZ; however, the improvement was overshadowed by a much larger improvement in the reaction impedance. 14 Although we observed that infiltrating a cobaltite with high electrocatalytic activity and oxygen ion conductivity lowered the cathode reaction impedance more than nanoYSZ, the combination of lower reaction and lower bulk charge transport impedance with nanoYSZ resulted in superior performance. While structural stability of nanoparticles is often a point of concern for performance degradation, here we show that the performance of the cell modified with nanoYSZ was three times more stable than that of the cell with PBC (Pr x Ba 1−x CoO 3−δ ).…”
mentioning
confidence: 67%
“…Upon calcination, the infiltrated particle size is typically distributed over a range of 20 nm to 80 nm and does not form percolated particle networks. [12][13][14][15][16] Infiltrating LSM-YSZ cathodes with LSCF, cobaltites, and doped cerias have all been shown to lower impedance to the electrocatalytic reaction in the cathode, [12][13][14][15][16] and the improvement is attributed to high electrocatalytic activity of the infiltrated particles located near LSM-YSZ active TPBs.…”
mentioning
confidence: 99%
“…Mixed conductive materials such as Ln 0.7 Sr 0.3 Fe 0.8 Co 0.2 O 3−δ (Ln = Pr, La, Gd) [41] are considered for improved oxygen conductivity and electrocatalytic activity. For operation at lower temperatures, La 0.5 Sr 0.5 CoO 3 [lanthanum strontium cobaltite (LSC)] was investigated [42], and La 0.8 Sr 0.2 Sc 0.1 Mn 0.9 O 3 [lanthanum strontium scandium manganite (LSSM)] [43] was specifically proposed for anode-supported SC-SOFCs.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…6 The most common approach has been to infiltrate mixed ionic-electronic conductors (MIECs), such as doped-cerias and doped-cobaltites, into the porous LSM-YSZ electrode, forming nanoparticles of MIECs on the LSM-YSZ surface. [6][7][8][9][10][11] These infiltrant modifications have been shown to lower the cathode reaction impedance and researchers ascribe the improvement to increasing both electrocatalytic activity and the effective density of active sites. [6][7][8][9][10][11] In our own work, we have recently shown that infiltrating YSZ nanoparticles into LSM-YSZ cathodes results in a lower total impedance and higher power density than infiltrating with praseodymium barium cobaltite (PBC) nanoparticles, a highly active MIEC.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] These infiltrant modifications have been shown to lower the cathode reaction impedance and researchers ascribe the improvement to increasing both electrocatalytic activity and the effective density of active sites. [6][7][8][9][10][11] In our own work, we have recently shown that infiltrating YSZ nanoparticles into LSM-YSZ cathodes results in a lower total impedance and higher power density than infiltrating with praseodymium barium cobaltite (PBC) nanoparticles, a highly active MIEC. 11 Importantly, the nano-YSZ was shown to significantly improve the impedance of both bulk charge transport (35% reduction) and the reaction processes (40% reduction), whereas PBC lowered the reaction impedance by 53% but only lowered the bulk charge transport impedance by 6%.…”
mentioning
confidence: 99%